The disappearing Christ : secularism in the silent era - Maciak, Phillip (Columbia University Press, 2019)
"At the turn of the twentieth century, American popular culture was booming with opportunities to see Jesus Christ. From the modernized eyewitness gospel of Ben-Hur to the widely circulated passion play films of Edison, Lumière, and Path ; from D.W. Griffith's conjuration of a spectral white savior in Birth of a Nation to W.E.B. Du Bois's 'Black Christ' story cycle, Jesus was constantly and inventively visualized across media, and especially in the new medium of film. Why, in an era traditionally defined by the triumph of secular ideologies and institutions, were so many artists rushing to film Christ's miracles and use his story and image to contextualize their experiences of modernity? In The Disappearing Christ, Phillip Maciak examines filmic depictions of Jesus to argue that cinema developed as a model technology of secularism, training viewers for belief in a secular age. Negotiating between the magic trick and the documentary image, the conflicting impulses of faith and skepticism, the emerging aesthetic of film in this period visualized the fraught process of secularization. Cinematic depictions of an appearing and disappearing Christ became a powerful vehicle for Americans to navigate a rapidly modernizing society. Studying these films alongside a multimedia, interdisciplinary archive of novels, photographs, illustrations, and works of theology, travel writing, and historiography, The Disappearing Christ offers a new narrative of American cultural history at the intersection of cinema studies and religious studies."--Provided by publisher.